Management of Orbital and Periorbital Venous Malformation - Benoiton, Lara A.; Chan, Kenneth; Steiner, Frederica; FitzJohn, Trevor; Tan, Swee T. (Frontiers in Surgery, 2017)
Background To review our management of common VM affecting the orbit and/or periorbital area. Methods Consecutive patients with orbital and/or periorbital VM were identified from our vascular anomalies database. Demographic details of the patients, anatomic site(s) affected, symptoms and signs, presence of a family history of VM, types of treatment(s) were collected, supplemented by chart review. Results 24 patients age 1-68 (mean, 30) years with orbital and/or periorbital VM presented with cosmetic concerns (n=17, 71%), distensibility (n=15, 63%), pain (n=9, 38%), diplopia (n=4, 17%) and spontaneous thrombosis (n=1, 8%). The VM caused globe dystopia (n=13, 54%), enophthalmos (n=6, 25%), proptosis (n=3, 12%), exotropia (n=3, 12%), and pseudoptosis with visual obstruction (n=3, 13%). 11 (46%) patients were managed conservatively. 13 (54%) patients underwent active treatment. Ethanol sclerotherapy (ES) was performed in six patients with extensive facial VM associated with orbital/periorbital involvement, resulting in symptomatic improvement in five patients, one of whom developed skin necrosis and another patient developed reduced infraorbital nerve sensation. Surgery was performed for localized lesion (n=3, 23%), for extensive lesions (n=4, 31%) and as an adjunct to ES (n=6, 46%) resulting in symptomatic improvement in all patients. One patient required correction of lower lid ectropion. Conclusion Orbital and/or periorbital VMs are heterogeneous and management needs to be individualized. Surgery is used for localized lesions aiming for complete excision, as a debulking procedure for extensive orbital/periorbital VM when ES was not possible, or following ES for extensive facial VM with orbital and/or periorbital involvement.